When Tuition Hikes, Students Fight: A Case on Business Ethics and Negotiation - Dreisbach, Jeconiah Louis (IIUM Journal of Case Studies in Management, 2020)
This case presents an ethical dilemma on the side of a newly-hired top executive, whose job was to negotiate an exorbitant amount of increase in the tuition and other school fees of the university that hired him. As outrage from the students and employees ensued, he took the initiative of reviewing the institution’s finances and found out its money-making venture, despite it being registered as a non-profit. As such, the executive resigned from his post and became a witness in a legal proceeding that was filed by the aggrieved parties against the university’s management. The anomaly was eventually settled with the university board providing additional seats for students and employees in the policy-making body